SHM_1206487_HST_3D Viking Age Iron Axe from Birka - National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of an iron axe from the Swedish Viking Age. Collected from Birka in Adelsö Parish in the province of Uppland, Sweden, it is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=1000

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C5B9D45B-E3C1-4D45-B98E-E74233B57FCF
Keywords: Archaeology; Archaeology; Archaeology/history; Photogrammetry; Dynamic Collections; 3D Model; Museum Object; Birka; Swedish Viking Age; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi